From the temple to the digital scene: Indian classical dance in pandemic times (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article addresses the actions taken through digital technologies in  support to Indian classical dances, as a result of the COVID-19 crisis. In particular regarding the styles Bharata Natyam and Kathak. It presents the processes developed in addition to remote classes and videos that were made available on the internet; such as debate forums, congresses, spaces for the acquisition and distribution of content and information. Ultimately, it discuss the contribution of digital media to Indian dance in an adverse pandemic context. How it expands some territories and constricts existing ones; opens up a whole field of research and creative activity that continues to grow, resulting in a new framework for production and reception of the Indian dance.
Keywords: Digital media; Pandemic; Indian Classical dance; Bharata natyam; Kathak